Aspects of hole-burning and spectro-temporal holography in molecular doped solids (Review Article): Molecular Solids - Galaup, Jean-Pierre (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The persistent spectral hole-burning (PSHB) phenomenon is known since 1974. It is still an important research area for the study of the intimacy of complex molecular systems in the solid state, revealing high resolution spectra, photophysics, photochemistry and dynamics of molecular doped amorphous media, organic as well as inorganic. From another point of view, PSHB allowsthe engraving of any spectral structures in the inhomogeneous absorption band profile of moleculardoped amorphous hosts or ion doped crystals cooled down to liquid helium temperatures. Therefore, a PSHB material is programmable in the spectral domain and consequently it can be transformed in an optical processor capable to achieve user-defined optical functions. Some aspects of both fields are illustrated in the present paper. Concerning the search of efficient PSHB materials, the hole burning performances and the photophysics of polymer and xerogel based systems are compared. The problem of high-temperature persistent spectral hole-burning materials and the search for new frequency selective photosensitive systems for fast optical pulse processing at 800 nm are considered. Regarding the points treated, inorganic hosts based on silicate xerogels or porous glasses have shown the best results. Moreover, by combining inorganic and organic capabilities or by grafting organic species to the host, hybrid xerogels have not yet revealed all possibilities. Also, the interest of two-photon materials for engraving spectral features with near-infrared or infrared light is developed. As an introduction to possible applications of PSHB material, the basics of spectro-temporal holography are remembered and a demonstrative experiment using a naphthalocyanine doped polymer film is described, proving that the temporal aberration free re-compression of ultrashort light pulses is feasible, therefore opening a way for applications in ultrashort light pulse shaping. Aspects for a comparison between cw hole-burning and femtosecond spectro-temporal experiments are considered and perspectives for the coherent control of light fields or photochemical processes are also evoked.